FUNCTIONAL AND RADIOLOGICAL OUTCOME OF TIBIAL PLATEAU FRACTURES MANAGED WITH INTERNAL FIXATION - NARAYANA, M LAKSHMI; NAGARAJU, K (Asian Journal of Pharmaceutical and Clinical Research, 2022)
Objectives: Tibial plateau fractures constitute a wide spectrum of severity from simple to complex fracture patterns. Treatment methods such as internal fixation and hybrid external fixation are commonly administered with specific limitations. The present study was designed to evaluate radiological and functional outcome of tibial plateau fractures managed with internal fixation. Methods: Thirty-six cases with tibial plateau fractures above 21 years were recruited. All the study cases were managed with open reduction and internal fixation. The post-operative follow-up was continued till 6 months with proper clinicoradiological evaluation to check range of motion, reduction loss, and fracture union. The functional outcome was assessed by Oxford Knee Society score and operative outcome was assessed by modified Rasmussen clinical and radiological criteria. Results: Functional outcome assessed by Oxford Knee Society score showed both excellent and good outcomes in 91.67% of cases cumulatively. Clinical outcome by modified Rasmussen assessment criteria reported excellent outcome in 33.33%, good in 44.44%, fair in 13.88%, and poor in 8.33%. Radiological outcome was excellent in 16.6%, good in 63.88%, fair in 11.11%, and poor in 8.33%. Conclusion: The post-operative functional, clinical, and radiological outcomes indicate that open or closed reduction and internal fixation had gained excellent results and are effective modalities in the management of tibial plateau fractures.